Perceived bitterness character of beer in relation to hop variety and the impact of hop aroma - Oladokun, Olayide; James, Sue; Cowley, Trevor; Dehrmann, Frieda; Smart, Katherine; Hort, Joanne; Cook, David (Elsevier, 2017)
The impact of hop variety and hop aroma on perceived beer bitterness intensity and character was investigated using analytical and sensory methods. Beers made from malt extract were hopped with 3 distinctive hop varieties (Hersbrucker, East Kent Goldings, Zeus) to achieve equi-bitter levels. A trained sensory panel determined the bitterness character profile of each singly-hopped beer using a novel lexicon. Results showed different bitterness character profiles for each beer, with hop aroma also found to change the hop variety-derived bitterness character profiles of the beer. Rank-rating evaluations further showed the significant effect of hop aroma on selected key bitterness character attributes, by increasing perceived harsh and lingering bitterness, astringency, and bitterness intensity via cross-modal flavour interactions. This study advances understanding of the complexity of beer bitterness perception by demonstrating that hop variety selection and hop aroma both impact significantly on the perceived intensity and character of this key sensory attribute.